Analysis of the Effect of Information and Communications Infrastructure on Foreign Direct Investment in Emerging Market Countries - Rizaldi, Mohammad Falakh; Jayadi, Akhmad (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2022)
This study examines the effect of information and communication technology infrastructure on foreign direct investment in 20 emerging market economies. In the 90s, developing countries had policies to make it easier for investors. Emerging markets countries are significant and potential markets. There is data that emerging market countries have increased from 35.90% to contributing 46.62% of FDI of the world's total in 2019. Using 25 years of data (1995-2019), use the panel data regression method to see the influence of ICT infrastructure on FDI. Find strong empirical evidence showing that the influence of ICT infrastructure on FDI is significantly positive in emerging market economies. In addition, we also examine the relationship between the variables GDP, inflation, and Trade openness to FDI. GDP, and Trade openness have significant positive results for FDI, while inflation has significant negative results for FDI in emerging market economies.